2017
DOI: 10.1007/978-3-319-51436-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia in Cystic Kidney Disease

Abstract: Primary cilia are small, antenna-like structures that detect mechanical and chemical cues and transduce extracellular signals. While mammalian primary cilia were first reported in the late 1800s, scientific interest in these sensory organelles has burgeoned since the beginning of the twenty-first century with recognition that primary cilia are essential to human health. Among the most common clinical manifestations of ciliary dysfunction are renal cysts. The molecular mechanisms underlying renal cystogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 289 publications
1
21
0
Order By: Relevance
“…All the above mentioned studies support the unifying theory of renal cystogenesis, coined more than 15 years ago, and further developed in later studies [17,136,137] According to this concept, mutations in genes expressed in primary cilia, basal bodies and centrosomes lead to dysfunction of cilia, thereby contributing to cell differentiation, stimulated proliferation and fluid secretion, as well as increased apoptosis of tubular cells, ultimately leading the development of cystic disease [17,136,137]. Further studies suggested that human ciliopathies could be caused by sorting defects at the transition zone and the ciliary gate [56].…”
Section: Sensenbrenner Syndromesupporting
confidence: 68%
See 2 more Smart Citations
“…All the above mentioned studies support the unifying theory of renal cystogenesis, coined more than 15 years ago, and further developed in later studies [17,136,137] According to this concept, mutations in genes expressed in primary cilia, basal bodies and centrosomes lead to dysfunction of cilia, thereby contributing to cell differentiation, stimulated proliferation and fluid secretion, as well as increased apoptosis of tubular cells, ultimately leading the development of cystic disease [17,136,137]. Further studies suggested that human ciliopathies could be caused by sorting defects at the transition zone and the ciliary gate [56].…”
Section: Sensenbrenner Syndromesupporting
confidence: 68%
“…Further studies suggested that human ciliopathies could be caused by sorting defects at the transition zone and the ciliary gate [56]. It was initially proposed that the key molecular events contributing to cystogenesis are increased intracellular cAMP [17], or activation of MAPK/ERK and mTOR pathways [138][139][140]. However, studies in murine ADPKD models excluded the causative role of these signaling cascades and demonstrated that formation of cysts is rather triggered by other cilia-dependent pathways [138].…”
Section: Sensenbrenner Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Two such spatially confined subcellular compartments are lipid rafts and cilia. In particular, the latter has been implicated in PKD (Avasthi et al, 2017;Ma et al, 2017;Pala et al, 2017). Both GPCRs and polycystin 1 are present in cilia (Yoder et al, 2002;Schou et al, 2015;Hilgendorf et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormality of the polycystic kidney disease (Pkd) 1 or Pkd2 genes, which encode polycystin-1 and polycystin-2, respectively, causes ADPKD; both polycystin-1 and polycystin-2 are transmembrane proteins and function in cell-cell/matrix interactions, tissue development, mechanical sensors, and calcium signaling (2). Cystic epithelial cells exhibit various physiologic aberrations, such as abnormal proliferation of renal epithelial cells (1), dysfunction of primary cilia (3)(4)(5), and dysregulation of extracellular matrix remodeling (6). In the molecular pathologic mechanism of cystic epithelia, several signal transduction pathways are known to be abnormal in cyst progression, including epidermal growth factor receptor (EGFR), mammalian target of rapamycin (mTOR), TGF-b/Smad, and the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway (7), and several molecules targeting these signaling pathways have been developed to decrease cyst expansion in mice PKD models.…”
mentioning
confidence: 99%